HIGIENE PENJAMAH MAKANAN DAN SANITASI KANTIN SEKOLAH DASAR NEGERI DI KECAMATAN MULYOREJO, SURABAYA - Sarah Syaﬁrah; Dini Ririn Andrias (Universitas Airlangga, 2015)
Food poisoning is one of health problems which caused by consumption of contaminated food. Application of hygiene and sanitation in the school canteen is a form of food contamination prevention. This study was aimed to describe hygiene of food handlers and sanitation of elementary school canteens in Mulyorejo subdistrict. This was a quantitative descriptive research. Population in this research was 13 elementary school canteens in Mulyorejo subdistrict. Purposive sampling was used in this study based on the food sold which were not packaged food as much as 9 canteens. The study showed that six food handlers (66,67%) had at least one infectious disease in the last three months. The majority of food handlers had good handwashing habit before touching foods (66,67%) and after contact with other substance (55,56%). The majority of food handlers (77,78%) had short and clean nail, also 88,89% wore clean and tidy cloths. The sanitation facilities that did not meet requirements of KEPMENKES No. 1098/MENKES/SK/VII/2003 were the availability of bins (88.89%) and handwashing place (100%). The Sanitary of food serving such as table serving (55.56%) and maximum limit of washed equipment (55.56%) are not eligible. The conclusion from this study is the hygiene of food handlers in the school canteens are generally good, while the overall condition of school canteens sanitation is less appropriate compare to the standards. This study recommends the urgency of sanitation facilities improvement in school canteens by school authorities of Mulyorejo subdistrict.Keywords: hygiene, canteen, food handlers, sanitation